Burn-out syndrome in Spanish internists during the COVID-19 outbreak and associated factors: a cross-sectional survey - Cristina Macía-Rodríguez; Álvaro Alejandre de Oña; Daniel Martín-Iglesias; Lucía Barrera-López; María Teresa Pérez-Sanz; Javier Moreno-Diaz; Adriana González-Munera (BMJ Open)
Objectives The objective of this study is to evaluate the impact of the COVID-19 outbreak on mental health and burn-out syndrome in Spanish internists and the factors that could be related to its appearance.Design We performed an observational, cross-sectional, descriptive study for which we designed a survey that was distributed in May 2020.Setting We included internists who worked in Spain during the COVID-19 outbreak.Participants A total of 1015 internists responded to the survey. Of those 62.9% were women.Results Of 1015 people, 58.3% presented with high emotional exhaustion, 61.5% had a high level of depersonalisation and 67.6% reported low personal fulfilment. 40.1% presented with the 3 criteria described, and therefore burn-out syndrome.Burn-out syndrome was independently related to the management of patients with SARS-CoV-2 (HR: 2.26; 95% CI 1.15 to 4.45), the lack of availability of personal protective equipment (HR: 1.41; 95% CI 1.05 to 1.91), increased responsibility (HR: 2.13; 95% CI 1.51 to 3.01), not having received financial compensation for overtime work (HR: 0.43; 95% CI 0.31 to 0.62), not having rested after 24-hour shifts (HR: 1.61; 95% CI 1.09 to 2.38), not having had holidays in the previous 6 months (HR: 1.36; 95% CI 1.01 to 1.84), consumption of sleeping pills (HR: 1.83; 95% CI 1.28 to 2.63) and higher alcohol intake (HR: 1.95; 95% CI 1.39 to 2.73).Conclusions During the COVID-19 outbreak, 40.1% of Internal Medicine physicians in Spain presented with burn-out syndrome, which was independently related to the assistance of patients with SARS-CoV-2, overworking without any compensation and the fear of being contagious to their relatives. Therefore, it is imperative to initiate programmes to prevent and treat burn-out in front-line physicians during the COVID-19 outbreak.